Сполуки сірки у складі моторних палив. вплив на навколишнє середовище під час експлуатації транспортних засобів - Медвєдєва, Т.В.; Іванов, С.В.; Бойченко, С.В. (Актуальні проблеми транспортної медицини, 2005)
Transport is one of the main sources of the atmospheric pollution. The requirement to the content of sulfur combinations in motor fuels has become tougher all over the world as its high concentration may result in many dangers both to the environment and human beings.